2015
DOI: 10.4269/ajtmh.14-0471
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Genetic Factors Determine Whether the Mosquito Aedes aegypti Lays Eggs Without a Blood Meal

Abstract: Abstract. Some mosquito strains or species are able to lay eggs without taking a blood meal, a trait named autogeny. This may allow populations to persist through times or places where vertebrate hosts are scarce. Autogenous egg production is highly dependent on the environment in some species, but the ideal conditions for its expression in Aedes aegypti mosquitoes are unknown. We found that 3.2% of females in a population of Ae. aegypti from Kenya were autogenous. Autogeny was strongly influenced by temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 34 publications
(45 reference statements)
1
15
0
1
Order By: Relevance
“…13 Several factors which correlated to the choice of the place where the female mosquito puts its eggs are the presence of other specific larvae or pupae, sun exposure and the size of the container. 14 Result of this study in accordance with previous studies which found Aedes sp. laid their eggs more outdoors than indoors.…”
Section: Discussionsupporting
confidence: 92%
“…13 Several factors which correlated to the choice of the place where the female mosquito puts its eggs are the presence of other specific larvae or pupae, sun exposure and the size of the container. 14 Result of this study in accordance with previous studies which found Aedes sp. laid their eggs more outdoors than indoors.…”
Section: Discussionsupporting
confidence: 92%
“…While males are polygynous, they limit fertilization by other males both by transferring sufficient sperm to fertilize all eggs a female will lay in her lifetime, and by transmitting accessory gland secretions that act as physical and chemical barriers to insemination by other males [reviewed by Oliva et al (2014)]. After mating, egg maturation generally occurs after blood feeding, but can occur in its absence in a small portion (3-4%) of females (Ariani et al 2015). A. aegypti does not have heteromorphic sex chromosomes among its three pairs of chromosomes (Juneja et al 2014).…”
mentioning
confidence: 99%
“…It is also 520 possible that mosquitoes in search of an oviposition site may have never taken a blood 521 meal. While most mosquitoes usually require a blood meal to develop eggs, autogeny 522 has been reported in these species (Ariani et al, 2015;Chambers and Klowden, 1994;523 Olejnícek and Gelbic, 2000). Autogeny rates, which are variable and depend on 524 temperature and nutrition, have been reported to range from 3 -34% for Ae.…”
Section: Discussion 485mentioning
confidence: 99%
“…aegypti, 525 around 5% for Ae. albopictus, and up to 87% in Culex mosquitoes (Ariani et al, 2015;526 Chambers and Klowden, 1994;Olejnícek and Gelbic, 2000;Trpis, 1977). Little is known 527 regarding the influence of microbiota and autogeny, although in the autogenous 528 mosquito Ae.…”
Section: Discussion 485mentioning
confidence: 99%